THU0309 Proteomic Differential Expressed Protein in Fibromyalgic Saliva: Comparison with Other Pain Model as Rheumathoid Arthritis and Migraine. (10th June 2014) - Giacomelli, C.; Ciregia, F.; Giusti, L.; Consensi, A.; Rossi, A.; Gori, S.; Bombardieri, S.; Lucacchini, A.; Bazzichi, L.
Abstract : Background: Fibromyalgia Syndrome (FM) is a chronic non inflammatory musculoskeletal disorder characterized by widespread pain and by the presence of at least 11 out of 18 specific tender points on physical examination and associated with a plethora of dysfunctional disorders. Currently no validated laboratory biomarkers are available for FM and the diagnosis of the disease remains exclusively clinical. Objectives: With the present study, we used two-dimensional electrophoresis (2DE) in combination with mass spectrometry (MS) to evaluate the global changes in salivary profile of FM patients. The aim was the search for any eventual diagnostic or prognostic salivary biomarkers which could be useful for the management of FM patients and compare the profile of FM with two different model of chronic pain: migraine patient such as non-inflammatory chronic pain and rheumathoid arthritis (RA) patients as inflammatory chronic pain. Methods: Samples were pooled according to their diagnosis, and submitted to 2DE. The gels were stained with Sypro and images analyzed performing a comparison between FM and control classes (healthy, rheumatoid arthritis, migraine). Proteins spots of interest were identified by NanoLC-ESI-MS/MS analysis. Results: The analysis of the protein profiles allowed us to find 26 spots with a different expression in FM respect to RA (p-value<0.05), 28 spots from the comparison of FM with migraine, and 32 in FM respect to healthy subjects. In particular, we found 7 spots differentially expressed exclusively in FM. Six spots were identified as serotransferrin and the other as alpha-enolase. Both serotransferrin and alpha-enolase increased in FM respect to all the control classes. Furthermore, the proteins differentially expressed in FM respect to the control classes, were functionally analyzed by using the Ingenuity Pathways Analysis software with the aim to determine the predominant canonical pathways and the interaction network involved. Serotransferrin is an iron binding transport protein, responsible for the transport of iron from sites of absorption to those of storage and utilization, and alpha-enolase is a multifunctional enzyme that, as well as its role in glycolysis, plays a part in various processes such as growth control, hypoxia tolerance and allergic responses. Moreover, serum transferrin plays an important role in inflammation, while alpha enolase stimulates immunoglobulin production. Therefore our results seem to support the inflammatory and a dis-regulation of immunity system hypothesis for FM. In fact, also the network built with our proteins highlights the involvement of inflammatory response in FM and the immune cell trafficking. In addition, proteomic profile of FM patients is more similar to that of RA patients, rather than migraine and healthy subjects. Conclusions: In conclusion, this study shows the presence of differentially expressed proteins in the saliva of FM patients, probably related to the disease. Consequently, the proteomic approach could be useful both to define a panel of potential diagnostic biomarkers and to shed new light on the comprehension of the pathogenetic pathways of FM. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3714